The correlation between the intensity of instagram usage and orthorexia nervosa in Universitas Gadjah Mada students - Tsania Fitri Kumala; Yayuk Hartriyanti; Aviria Ermamilia (Penerbit Universiti Kebangsaan Malaysia, 2024)
Background: Orthorexia nervosa (ON) is an eating disorder characterized by an obsession with eating healthy foods, which has physical, psychological, and social impacts. The use of social media platform such as Instagram is suspected to be one of the risk factors of ON, as health information on Instagram can reach thousands of people despite the fact that its source is frequently unreliable. Objective: To determine the correlation between the intensity of Instagram usage and ON among Universitas Gadjah Mada (UGM) students, as well as the correlation between confounding variables (gender, monthly income, age, faculty cluster, and nutritional knowledge) and ON. Methods: The research design used is an observational study with cross-sectional design that involved 529 students. Samples were taken by stratified random sampling, and data was collected online. Chi square test with ꭤ = 0.05 was used in this study. Results: The results showed that as many as 55% of students were diagnosed with ON and most of the students had moderate intensity of using Instagram. There is a correlation between the intensity of using social media Instagram and ON in UGM students (p value = 0.037<0.05) and there is no correlation of confounding variables (gender, monthly income, age, faculty cluster, and nutritional knowledge) with ON. Conclusion: There is a positive correlation between the intensity of Instagram use and ON in UGM students, and no confounding variables were found in this study.